The role of DSPF, the type III secretion chaperone of DspA/E of Erwinia amylovora, in pathogenicity in host and non-host plants - Aksoy, Hasan Murad; Kaya, Yilmaz; Tengku Abdul Hamid, Tengku Haziyamin (Pakistan Agricultural Scientists Forum, 2017)
Erwinia amylovora is a Gram-negative enterobacterium that causes a devastating blight disease on rosaceous plants. In this study, the structure of DspF, a type III secretion system (T3SS) chaperone required for virulence of E. amylovora, was investigated in bacterial growth and pathogenesis in host and non-host plants, including apple, strawberry, rose, Arabidopsis and tobacco. DspF genes were mutated through homologous recombination and the result was the arrest of disease development on apple, strawberry and rose, and of the hypersensitivity response in tobacco. In addition, bacterial development of the wild type was compared with that of dspF mutants in leaves of A. thaliana Columbia-5 (Col-5), and the resistant A. thaliana Landsberg erecta (Ler-0). It was concluded that DspF is essential for the bacterium to induce hypersensitive responce (HR) disease on host plants (Rosaceous family plant) and non-host plants (Arabidopsis thaliana).